1988
DOI: 10.1073/pnas.85.15.5597
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of America by Drosophila subobscura : Experiment in natural populations that supports the adaptive role of chromosomal-inversion polymorphism

Abstract: North America and South America have recently been colonized by the Palearctic species Drosophila subobscura. This double colonization offers a rare opportunity for evolutionary studies. Correlations between chromosomal arrangement frequencies and latitude were calculated for the colonizing populations. Signs of these correlations are highly coincident with those found in the Old World. These results provide experimental support for the adaptive value of the chromosomal-inversion polymorphism; historical and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
235
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(260 citation statements)
references
References 7 publications
16
235
0
1
Order By: Relevance
“…This result is consistent with earlier findings on genetic variability in the intercontinental spread of this species (Latorre et al 1986;Prevosti et al 1988;Rozas et al 1990;Rozas and Aguade 1991;Balanya et al 1994). In contrast, we found no significant loss of heterozygosity or number of alleles in the eastward spread of D. subobscura from the west coast of North America.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This result is consistent with earlier findings on genetic variability in the intercontinental spread of this species (Latorre et al 1986;Prevosti et al 1988;Rozas et al 1990;Rozas and Aguade 1991;Balanya et al 1994). In contrast, we found no significant loss of heterozygosity or number of alleles in the eastward spread of D. subobscura from the west coast of North America.…”
Section: Discussionsupporting
confidence: 82%
“…These findings are consistent with genetic drift causing allele frequency differences between populations in the eastward spread of D. subobscura across North America, as by founder effect(s). We do not think that selection acting on chromosomal inversions in this species contributed to these results, given the genetic similarity between the distant west coast populations, the observed association of inversion arrangements with latitude (Prevosti et al 1988), and the lack of significant clines in North American populations for inversions on the A-chromosome (Ayala et al 1989).…”
Section: Nuclear Microsatellite and Mitochondrial Dna Restriction Framentioning
confidence: 91%
See 1 more Smart Citation
“…In species of Drosophila where a clinal variation for inversions was found, notably in D. subobscura (Prevosti et al 1988), the clines have tended to reproduce wherever this species was transported accidentally by human transport. In fact, a north-south cline for paracentric inversions in Europe has repeated itself in the Pacific coast of North America, and it reversed and became a south-north cline in the Pacific coast of South America.…”
Section: The Central-marginal Model In Robertsonian Polymorphic Grassmentioning
confidence: 99%
“…One of the most striking examples may be the 'replicated time series of evolution in action' in Drosophila subobscura (Prevosti et al, 1988;Gilchrist et al, 2004), but other fascinating cases have also been identified in other animal species (for example, grasshoppers in Shaw et al, 1985;Drosophila in Hoffman et al, 2004; Anopheles in Coluzzi et al, 2002;humans in Stefansson et al, 2005). In some instances, adaptive gradients may result in considerable divergence such that they finally lead to speciation (for example, Drosophila: Noor et al, 2001;Machado et al, 2002;Anopheles: Coluzzi et al, 2002;Rhagoletis: Feder et al, 2005).…”
Section: Introductionmentioning
confidence: 99%